Antimicrobial Pattern of Foodborne Bacterial Hazards Isolated from Vegetables in Dhaka City - Zaman, Sharmin; Bari, Md Latiful (Journal of Science and Technology Research, 2024)
The prevalence of undesirable microbial contaminants in fresh vegetables, often consumed raw as salad vegetables, is a concern for the global public health community. In this study, samples from different local markets in Dhaka were collected to evaluate the microbiological quality and safety of four raw salad vegetables, namely, lettuce, tomato, cucumber, and coriander leaves. Microbiological analyses revealed a higher total aerobic bacterial count (3.10 to 8.71 log CFU/g) and coliform count (non-detectable to 7.61 log CFU/g) regardless of RSV type. In all of the examined shop types, foodborne pathogens like Escherichia coli and Salmonella spp. were found in more than 60% of the analyzed vegetable samples, and the isolated E. coli and Salmonella spp. were found to be completely resistant to 3 different antibiotics (Amoxicillin, Erythromycin, and Rifampicin) and intermediately resistant to 2 other antibiotics (Bacitracin and Novobiocin). Therefore, the study findings revealed that the presence of multidrug-resistant E. coli and Salmonella spp. in fresh vegetable samples is a cause for worry when consumed raw. Controlled environment production approaches, such as indoor farming of vegetables and washing with plenty of fresh water before consumption, can help to reduce pathogen and antimicrobial resistance bacteria. J. of Sci. and Tech. Res. 6(1): 45-51, 2024